(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
Over the past century, Greater Khartoum witnessed five urban planning schemes geared to direct its growth and development for an average of two decades each. Those master and structure plans addressed primarily its land use and transportation issues with some attention paid to environmental issues. This study develops an alternative vision for Greater Khartoum and charts a distinctive path for its future development that aims to maximize its natural assets, to enrich its urban image and to propose measures to safeguard its unique environmental qualities. Such a vision is not a stand-alone exercise, nor developed in a vacuum. Rather, its point of departure is the most recent master plan, KPP5 of 2008, to which the proposed vision relates. The study proposes a vision for what the city is capable of evolving into in the coming decades. It investigates the essential components of urban planning â€“ namely, land use, housing, transportation, infrastructure and social services â€“ all within an enriching environmental framework. The methodology used in this study includes a thorough review of urbanization trends and past urban development plans for Greater Khartoum, review of environmental laws, strategies and acts that impinge upon urban development in Greater Khartoum, and facilitating the formulation of an alternative vision by a sample of young generations and future residents of Greater Khartoum â€“ including high school students, university students, recent graduates from both genders. Such visions, as the study concludes, are different, optimistic and more creative when compared with those espoused by older generations and professionals who developed the previous master plans. Special participatory workshops were organized where young participants were given the chance to express their visions verbally, in writing and through sketches. The principal investigators then compiled the main features and highlight of those budding visions into an alternative vision for Greater Khartoum â€“ one that reconciles its unlimited appetite for urban land with the desires of its future residents for a pleasant city where all essential amenities are engulfed within a cleaner and "greenerâ€ environment. This study though not comprehensive enough, identifies trends of how future generations envision Khartoum in 2030. The study concludes by providing some recommendations that pave the way to the realization of that vision as well as to ensure the sustainability of suggested urban changes and transformations.